Prevalence of Anemia and Undernutrition of Adolescent Females in Selected Schools in Ghana - Marina Aferiba Tandoh; Abigail Owusuaa Appiah; Anthony Kwaku Edusei (Journal of Nutrition and Metabolism)
Anemia among adolescent females is a major worldwide public health problem which should be given appropriate attention. Half of all anemic cases are caused by iron deficiency. In addition to anemia, poor nutrition is also a challenge in sub-Saharan Africa. This study determined the prevalence of anemia and undernutrition among adolescent females in school. A cross-sectional study was conducted among 151 adolescent females in four basic schools in the Ahafo region of Ghana. The hemoglobin level and anthropometry measures of participants were taken to determine their anemic and nutritional status. The prevalence of anemia among adolescent females in school was 50.3%. Out of the 151 participants, 6.6%, 19.9%, and 23.8% were severely anemic, moderately anemic, or mildly anemic, respectively. Only 2% of the participants were underweight, but the rate of stunting was 26.5%. The notable high prevalence of anemia that was found among adolescent females was correlated with other health and wellness concerns. Anemia and under nutrition negatively affect academic performance, productivity, and general wellbeing of adolescents; therefore, effective measures should be put in place to correct and eradicate these nutritional problems.